IT software purchase decisions in terms of business customer experience - Szwajlik, Anna (Human Technology, 2023)
The aim of this study is to compare experience of customers making decisions in teams and individually during the process of purchasing IT software supporting management processes in their organization.The research sample consisted of 114 companies from all over Poland that purchased management-supporting software in the last 3 years. Quantitative research method was used to achieve the adopted research objective. A questionnaire was applied as a research tool, while Manna-Whitney U test - was used to determine differences in experiment levels.This article refers to the models of organizational behavior, paying special attention to group and individual factors that business customer experience. The research results show that the experience of people who decide to purchase software as a team is better at all stages of the decision-making process compared to the experience of people making decisions individually.The collected research material, and, above all, the conclusions drawn from it, contribute to the knowledge about the quality of business customer experience in the IT sector, and outline the differences in the quality of such experience between those making decisions in the organization in a team and in an individual manner.